2013
DOI: 10.3892/or.2013.2506
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor promotes the migration and invasion of upper urinary tract urothelial carcinoma cells through the upregulation of MMP-9 and COX-2

Abstract: Dysregulated androgen receptor (AR) signaling is implicated in several types of tumor, including carcinomas of the prostate, breast, liver and bladder. However, the contribution of AR to the progression of upper urinary tract urothelial carcinomas (UUTUC) has not been fully investigated. In the present study, we demonstrated that the AR is involved in the metastasis and invasiveness of UUTUC cells. We investigated the role of the AR in UUTUC by using UUTUC-derived BFTC 909 cells. The overexpression of AR promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…64 Overexpression of AR has been associated with tumour cell migration and invasion in UTUC cell lines, suggesting AR could be a therapeutic target in patients who are positive for AR expression (Figure 2). 65 Currently, available data are still not sufficient to make any conclusions concerning the effect of gender in patients with UTUC. However, male patients seem to have a higher incidence of the disease, whereas survival might be independent of gender.…”
Section: Gender Differences In Utucmentioning
confidence: 99%
“…64 Overexpression of AR has been associated with tumour cell migration and invasion in UTUC cell lines, suggesting AR could be a therapeutic target in patients who are positive for AR expression (Figure 2). 65 Currently, available data are still not sufficient to make any conclusions concerning the effect of gender in patients with UTUC. However, male patients seem to have a higher incidence of the disease, whereas survival might be independent of gender.…”
Section: Gender Differences In Utucmentioning
confidence: 99%
“…molecules including vascular endothelial growth factors, cyclooxygenase, and matrix metalloproteins via stability of their mRNA (26)(27)(28)(29). These HuR-related molecules play important roles in carcinogenesis, cancer cell proliferation, angiogenesis, and tumor invasion in UC (30)(31)(32)(33). In fact, HuR was reportedly associated with metastasis and survival via the regulation of cancer cell proliferation, angiogenesis, and expression of vascular endothelial growth factor-A and -C in BC patients (17).…”
Section: Discussionmentioning
confidence: 99%
“…AR roles in migration/invasion of UUTUC cells and its linkage to chemotherapy UUTUC patients with locally advanced and poorly differentiated tumors may have a poorer outcome since they may experience disease recurrence and subsequently die from metastatic UUTUC. 57,62 Chen et al 63 found that addition of functional AR into UUTUC transformed cell lines, SV-HUC and BFTC 909, led to increased cell migration and invasion that might be mediated by the upregulation of the metastasis-related genes, matrix metalloproteinase-9, Rock-1 and Cox 2 by the AR. Targeting the AR with ASC-J9, in the UUTUC BFTC 909 cells resulted in increased cell sensitivity to both chemotherapeuic agents, doxorubicin and mitomycin C. 63 Hsieh et al 64 also found that addition of the AR in BFTC 909 cells increased cell viability on treatment with chemotherapeutic agents, cisplatin and doxorubicin, an effect that might be mediated through modulation of the membrane transporter protein ABCG2, a multi-drug chemoresistance factor in cancer cells.…”
Section: Ar Expression In Uutuc Cancermentioning
confidence: 99%